Integration of sepsis Bundles into the nursing process (Research, Society and Development, 2022)
Objective: Identify in the literature how the sepsis Bundles are integrated into the nursing process. Method: Integrative review, from 2015 to 2020, in the databases BDENF, MEDLINE, LILACS via VHL and SCIELO, in Portuguese. Eligible studies were discussed and presented in tables. Results: of the 10 eligible studies, 60% presented level IV of evidence and pointed to 3 different approaches: the importance of nurses in the face of sepsis; fundamental role of continuing education and training of nurses to sepsis and the emerging need to integrate the Sepsis Bundle into the nursing process. Conclusion: It was found academic and professional fragility of nursing in the face of sepsis, suggesting investment in education and training on the subject of teaching and care institutions. There are research gaps that integrate the sepsis Bundle into the nursing process, it is recommended to develop new research with a high level of evidence contributing to evidence-based practice.